1990
DOI: 10.1111/j.1440-1681.1990.tb01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetylcholine and Morphine on Bronchial Smooth Muscle Contraction and Its Modulation by Steroid Hormones

Abstract: 1. The effects of corticosteroid pretreatment on acetylcholine (ACH)-induced contraction of bronchial smooth muscle (BSM) were studied. 2. ACH dose-response curves for dexamethasone (DM)- and corticosterone (B)-treated but not deoxycorticosterone (DOC)-treated BSM were significantly shifted to the right; this provides evidence that glucocorticoid treatment reduced the sensitivity of BSM to ACH. 3. Morphine enhanced BSM contraction in response to ACH by 20%. DM suppressed this enhancement. 4. These findings cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The observation that dexamethasone can apparently increase the expression of some receptor subtypes and inhibit the expression of other receptor subtypes in different tissues suggests that cell-specific factors as well as gene-specific regulatory elements must be important in determining the effects of dexamethasone upon expression of G protein-coupled receptor genes in a given system. In the airways, dexamethasone inhibits inflammatory responses and also can reduce the responsiveness of airway smooth muscle ex vivo to contractile agonists (Nabishah et al, 1990). Our results suggest a possible mechanism to account for this latter effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that dexamethasone can apparently increase the expression of some receptor subtypes and inhibit the expression of other receptor subtypes in different tissues suggests that cell-specific factors as well as gene-specific regulatory elements must be important in determining the effects of dexamethasone upon expression of G protein-coupled receptor genes in a given system. In the airways, dexamethasone inhibits inflammatory responses and also can reduce the responsiveness of airway smooth muscle ex vivo to contractile agonists (Nabishah et al, 1990). Our results suggest a possible mechanism to account for this latter effect.…”
Section: Discussionmentioning
confidence: 99%
“…High local concentrations of corticosteroids may be present in the airways of patients receiving nebulised steroid therapy for asthma. We have been interested in the observation that preincubation of airway smooth muscle preparations with corticosteroids reduces the contractile response of the tissue when subsequently stimulated with contractile agonist (Nabishah et al, 1990). The mechanisms underlying this response are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro in bronchial smooth muscle, dose responses to acetylcholine were significantly shifted to the right by dexamethasone (17). In vivo in the guinea pig, dexamethasone inhibited acetylcholine-induced bronchoconstriction, and further studies in dogs showed that treatment with methylprednisolone increased sensitivity to ␤ 2 -agonistϪinduced bronchodilation.…”
Section: Effect Of Cs On Muscarinic Receptorsmentioning
confidence: 91%
“…The increase in 0-and P-adrenergic receptors in the hyperthyroid state (Ciaraldi & Marinetti 1977) may explain the adrenergic hyperactivity observed in hyperthyroidism. We have also demonstrated that glucocorticoids decrease the concentration of muscarinic receptors (Nabishah et al 1991) as well as the contractility of bronchial smooth muscle (Nabishah et al 1990b).…”
Section: Introductionmentioning
confidence: 63%
“…Preparations of bronchial smooth muscle for contractile response studies have been explained previously (Nabishah et al 1990b). Briefly, second generation bronchial smooth muscle was isolated and cut spirally, then placed in an organ bath containing 30 mL Krebs' solution bubbled with 5% COZ in 0 2 .…”
Section: Methodsmentioning
confidence: 99%